Analisis Peran Petugas Lapangan Keluarga Berencana dalam Meningkatkan Jumlah Akseptor “MJKP” - Jusriani, Jusriani; Rifai , Muhammad; Juhanto , Asrijun (Jurnal Sains & Kesehatan, 2022)
Data from the Lasusua Health Center, Lasusua District, North Kolaka Regency in 2020 the number of couples of childbearing age who use contraception is 3321 people and those who use "MKJP" are 762 people. This study aims to determine the extent of the analysis of the role of family planning field officers in increasing the number of "MKJP" acceptors through a formal approach, family planning services, family planning acceptors and non-acceptors of family planning. This qualitative research was carried out in the Work Area of the Lasusua Health Center, North Kolaka Regency, applying the number of informants as many as 9 people. Data was collected by means of in-depth interviews regarding the role of family planning field officers in increasing the number of “MKJP” acceptors.The results showed that the formal approach taken by PLKB was as usual, namely providing a counseling schedule and also participating in the success of the MKJP program. Family planning services provided by PLKB have been very good and what is the target of PLKB in increasing the use of MKJP has received a positive response from the community, especially those who use long-term contraception. PLKB has carried out its duties and functions according to its competence and PLKB also often goes directly to the homes of residents who use contraception or those who do not use contraception and in general the reasons for refusing to use contraception are due to cultural and religious factors. For this reason, it is necessary to collaborate with related parties to be more active in promoting long-term contraceptive use programs. It is expected that midwives who work in the KB poly section will further improve their performance and attention in providing counseling, especially regarding communication with family planning field officers (PLKB).